Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1289/ehp.1409177
|View full text |Cite
|
Sign up to set email alerts
|

Uses of NHANES Biomarker Data for Chemical Risk Assessment: Trends, Challenges, and Opportunities

Abstract: BackgroundEach year, the U.S. NHANES measures hundreds of chemical biomarkers in samples from thousands of study participants. These biomarker measurements are used to establish population reference ranges, track exposure trends, identify population subsets with elevated exposures, and prioritize research needs. There is now interest in further utilizing the NHANES data to inform chemical risk assessments.ObjectivesThis article highlights a) the extent to which U.S. NHANES chemical biomarker data have been eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 52 publications
0
56
0
Order By: Relevance
“…This program includes limited assessment of the sources or routes of exposure, but identifies individual, rather than combinations of, environmental chemicals of significance in blood and urine specimens [Centers for Disease Control and Prevention (CDC) 2009]. Recent studies showed that the NHANES data may also be used for further research on co-exposure to multiple chemicals in the U.S. population (Qian et al 2015; Sobus et al 2015; Woodruff et al 2011). The objective of this investigation was to examine co-exposure to multiple metals and their species in the NHANES population to provide background data for future studies of potential metal interactions.…”
Section: Introductionmentioning
confidence: 99%
“…This program includes limited assessment of the sources or routes of exposure, but identifies individual, rather than combinations of, environmental chemicals of significance in blood and urine specimens [Centers for Disease Control and Prevention (CDC) 2009]. Recent studies showed that the NHANES data may also be used for further research on co-exposure to multiple chemicals in the U.S. population (Qian et al 2015; Sobus et al 2015; Woodruff et al 2011). The objective of this investigation was to examine co-exposure to multiple metals and their species in the NHANES population to provide background data for future studies of potential metal interactions.…”
Section: Introductionmentioning
confidence: 99%
“…General population human biomonitoring programs are particularly useful for investigating such exposures (CDC 2015; Haines and Murray, 2012; Schulz et al, 2007). Interestingly, many contemporary chemicals are not persistent in people, and exposure biomarkers in urine are increasingly used to evaluate exposures to these compounds and to inform chemical risk assessments (Sobus et al, 2015). Compared to blood and other matrices, collecting urine is generally considered a non-invasive and relatively easy procedure, at least for adults.…”
Section: Introductionmentioning
confidence: 99%
“…The combined use of biomarkers of exposure and biomarkers of effect has also become a central theme for linking the external environment to potential adverse health outcomes [6][7][8]. There are now large databases such as the U.S. National Health and Nutrition Examination Survey (NHANES), the German Environmental Survey (Ger ES), The Korea National Health and Nutrition Examination Survey (KNHANES), and the Canadian Health Measures Study (CHMS) that are making such data mining readily available to the research community [9][10][11][12]. These are based on detailed analyses of thousands of "snapshot" measures from stratified random selections of subjects from the general populations of the respective countries.…”
Section: Introductionmentioning
confidence: 99%